Time pressured deprioritization of COPD in primary care: a qualitative study. (2nd January 2016) - Sandelowsky, Hanna; Hylander, Ingrid; Krakau, Ingvar; Modin, Sonja; Ställberg, Björn; Nager, Anna
Abstract: Objective: To identify factors that hinder discussions regarding chronic obstructive pulmonary disease (COPD) between primary care physicians (PCPs) and their patients in Sweden.Setting: Primary health care centres (PHCCs) in Stockholm, Sweden.Subjects: A total of 59 PCPs.Design: Semi-structured individual and focus-group interviews between 2012 and 2014. Data were analysed inspired by grounded theory methods (GTM).Results: Time-pressured patient–doctor consultations lead to deprioritization of COPD. During unscheduled visits, deprioritization resulted from focusing only on acute health concerns, while during routine care visits, COPD was deprioritized in multi-morbid patients. The reasons PCPs gave for deprioritizing COPD are: "Not becoming aware of COPD", "Not becoming concerned due to clinical features", "Insufficient local routines for COPD care", "Negative personal attitudes and views about COPD", "Managing diagnoses one at a time", and "Perceiving a patient's motivation as low''.Conclusions: De-prioritization of COPD was discovered during PCP consultations and several factors were identified associated with time constraints and multi-morbidity. A holistic consultation approach is suggested, plus extended consultation time for multi-morbid patients, and better documentation and local routines. Key points: Under-diagnosis and insufficient management of chronic obstructive pulmonary disease (COPD) are common in primary health care. A patient–doctor consultation offers a key opportunity to identify and provide COPD care. Time pressure, due to either high number of patients or multi-morbidity, leads to omission or deprioritization of COPD during consultation. Deprioritization occurs due to lack of awareness, concern, and local routines, negative personal views, non-holistic consultation approach, and low patient motivation. Better local routines, extended consultation time, and a holistic approach are needed when managing multi-morbid patients with COPD.